Association of insertion/deletion polymorphism of angiotensin-converting enzyme gene among Malay male hypertensive subjects in response to ACE inhibitors. (December 2015) - Heidari, Farzad; Vasudevan, Ramachandran; Mohd Ali, Siti Zubaidah; Ismail, Patimah; Etemad, Ali; Pishva, Seyyed Reza; Othman, Fauziah; Bakar, Suhaili Abu
Introduction: Several studies show that the insertion/deletion (I/D) polymorphism of the angiotensin-converting enzyme (ACE) gene has been associated with hypertension in various populations. The present study sought to determine the association of the I/D gene polymorphism among Malay male essential hypertensive subjects in response to ACE inhibitors (enalapril and lisinopril). Materials and methods: A total of 72 patients with newly diagnosed hypertension and 72 healthy subjects were recruited in this study. Blood pressure was recorded from 0 to 24 weeks of treatment with enalapril or lisinopril. Genotyping of the I/D polymorphism was carried out using a standard PCR method. Results: Statistically significant association of the D allele of the ACE gene was observed between the case and control subjects ( p < 0.01). There was a decrease in blood pressure in the patients carrying the DD genotype (SBP=18.5±8.1 mmHg, DBP=15.29±7.1 mmHg) rather than the ID (SBP=4.1±3.3 mmHg, DBP=9.1±3.5 mmHg) and II genotypes (SBP= 3.0±0.2 mmHg, DBP 0.11±6.1 mmHg) of the ACE gene. Conclusion: Patients carrying the DD genotype had higher blood pressure-lowering response when treated with ACE inhibitors enalapril or lisinopril than those carrying ID and II genotypes, suggesting that the D allele may be a possible genetic marker for essential hypertension among Malay male subjects.